ASSOCIATION OF PROGESTIN-ONLY INJECTABLE CONTRACEPTION USE WITH THE ODDS OF CEREBRAL MENINGIOMA DEVELOPMENT - Ruri Alifiana Maharani; Muhammad Yusuf; Ratna Dwi Jayanti (Indonesian Midwifery and Health Sciences Journal, 2026)
Background: The estimated occurrence and mortality rates of Central Nervous System (CNS) tumors in Indonesia in 2016 were 6,337 and 5,405, respectively. Based on medical record data from Dr. Soetomo General Hospital, Surabaya, for the period of 2017-2021, there were 1,192 meningioma patients. The manifestation of meningioma linked with age and is 2.3 times higher in women than in men. Sex hormones are considered one of the risk factors for meningioma development. The medroxyprogesterone injectable contraceptive is the most widely used type of contraception in Indonesia. The majority of contraceptives used by meningioma patients at Dr. Soetomo General Hospital during the 2012-2016 period were hormonal contraceptives of the progestin-only type. This study aims to analyze the association between the history of using progestin-only injectable hormonal contraception and the odds of cerebral meningioma among female patients at Dr. Soetomo General Hospital, Surabaya, during the 2020-2024 period. Methods: This study uses a retrospective case-control approach. The sample size was 30 subjects for the case group (cerebral meningioma) and 30 subject for the control group. The control group (Non-Cerebral Meningioma) is maintained, but these limitations are acknowledged in the discussion. An independent variable is a 3-month history of injectable contraceptive use (progestin-only), which is defined in more detail by duration and recentness. The sampling technique used was total sampling. The research instrument utilized was electronic medical records. The data analysis uses the Chi-square and Multivariate Binary Logistic Regression tests to calculate the Adjusted Odds Ratio (OR) with a 95% Confidence Interval. Results: The results indicated a highly significant association between the history of 3-month injectable contraception use and cerebral meningioma incidence (p < 0.001). Further stratification analysis revealed an adjusted Odds Ratio (OR) of 6.00 (95% CI: 1.17–30.73) for the history of exposure and 1.58 (95% CI: 1.08–2.30) for the duration of use. Although the risk estimates adjusted during stratification, both factors remained statistically significant risk indicators. Conclusion: The data suggest a strong association between a 3-month history of injectable contraceptive use with greater odds of developing cerebral meningioma.